The Transseptal Arthroscopic Knee Portal Is in Close Proximity to the Popliteal Artery: A Cadaveric Study - Cancienne, Jourdan M.; Werner, Brian C.; Burrus, M. Tyrrell; Kandil, Abdurrahman; Conte, Evan J.; Gwathmey, Frank W.; Miller, Mark D. (The Journal of Knee Surgery, 2017)
The purpose of this study was to use fluoroscopy to measure the distance between the transseptal portal and the popliteal artery under arthroscopic conditions with an intact posterior knee capsule, and to determine the difference between 90 degrees of knee flexion and full extension. The popliteal artery of eight fresh-frozen cadaveric knees was dissected and cannulated proximal to the knee joint. The posterolateral, posteromedial, and transseptal portals were then established at 90 degrees of flexion. A 4-mm switching stick was placed through the transseptal portal, and barium contrast was injected into the popliteal artery. A lateral fluoroscopic image was taken with the knee in 90 degrees of flexion and full extension, and the distance between the popliteal artery and the switching stick was measured and compared using a paired t-test. In knee flexion, the average distance between the transseptal portal and the anterior aspect of the popliteal artery for the eight cadaveric specimens was 12.0 mm ± 3.3 mm; in extension, this decreased to 9.0 mm ± 2.7 mm. The distance between the transseptal portal and popliteal artery was significantly higher at 90 degrees of knee flexion as compared with extension (p = 0.0005). The transseptal posterior knee arthroscopic portal must be carefully created due to the close proximity to the popliteal artery, and may be closer to the artery than previously reported in specimens with an intact posterior knee capsule. Creating the portal with the knee in flexion significantly displaces the popliteal artery away from the portal reducing the risk of arterial injury.
Keywords: transseptal portal; knee arthroscopy; popliteal artery; complications